With the common $\text{BigM}$ approach, we can linearize the logical expression as follows:
$$ if: \quad (x_{t}-x_{t-1} = 0) \implies (y_{i,t} - y_{i,t-1} = 0) \quad \equiv$$
$$ if: \quad (x_{t}-x_{t-1} = 0) \implies (z_{i,t} = 1) \implies(y_{i,t} - y_{i,t-1} = 0) \quad \equiv$$
The first part would be:
$$ if: \quad (z_{i,t} = 0) \implies ((x_{t}-x_{t-1} \geq 1) \lor (x_{t}-x_{t-1} \leq -1)) \quad \equiv$$
$$ if: \quad (z_{i,t} = 0) \implies (((w_{t} = 1) \implies (x_{t}-x_{t-1} \geq 1)) \lor ((o_{t} = 1) \implies (x_{t}-x_{t-1} \leq -1))) \quad \equiv$$
That yields the following three linear expressions:
$$ z_{i,t} + w_{t} + o_{t} \geq 1 \quad (1) $$
$$ x_{t} - x_{t-1} \geq 1 - m(1-w_{t}) \quad (2) $$
$$ x_{t} - x_{t-1} \leq -1 + M(1-o_{t}) \quad (3) $$
The second part also would be:
$$ (z_{i,t} = 1) \implies(y_{i,t} - y_{i,t-1} = 0) \quad $$
That translating into the following expressions:
$$ y_{i,t} - y_{i,t-1} \geq 0 - m(1-z_{i,t}) \quad (4) $$
$$ y_{i,t} - y_{i,t-1} \leq 0 + M(1-z_{i,t}) \quad (5) $$
Where the value of $m$ and $M$ should be $\leq 2$.
Also, based on the indicator variables the corresponding CNF is:
$$ (z_{i,t}) \bigvee ((x_{t} \land \lnot x_{t-1}) \lor (\lnot x_{t} \land x_{t-1})) $$
Thant yields following inequalities:
$$ z_{i,t} + x_{t} + x_{t-1} \geq 1 \quad (1) $$
$$ z_{i,t} - x_{t} - x_{t-1} \geq -1 \quad (2) $$
And the second part would be:
$$ (\lnot z_{i,t}) \bigvee ((y_{i,t} \land y_{i,t-1}) \lor (\lnot y_{i,t} \land \lnot y_{i,t-1})) $$
Thant yields following inequalities:
$$ -z_{i,t} + y_{i,t} - y_{i,t-1} \geq -1 \quad (1) $$
$$ -z_{i,t} - y_{i,t} + y_{i,t-1} \geq -1 \quad (2) $$